Socio-demographic characteristics and quality of life among women in the 3rd trimester of pregnancy living in Erzurum city center - Elif Oksan Calikoglu; Esra Cinar Tanriverdi; Sara Salcan; Hilal Betul Akcay; Duygu Kavuncuoglu; Ezel Bilge Yerli (SERNEV, 2018)
Introduction: In this research, it is aimed to determine therelationship between quality of life and socio-demographic variables in thethird trimester of pregnancy in Erzurum.Methods: Thestudy was conducted as a descriptive field survey between 1 December 2016 and31 January 2017. The universe of the research is composed of 226 pregnant womenin Erzurum city center. SPSSfor data recording and analysis. Ver.22.0 package program is used. Descriptivestatistics are presented as mean ± standard deviation, percent and frequencydistributions. The Mann Whitney-U test was used to assess the quality of lifeand p lt;0.05 was considered statistically significant.Results: All pregnant women in this studyare at least 28 weeks in pregnancy. The mean age of the women participating inthe survey is 28.2±5.8 (18-44) and 4% of them are 19 years old or younger. Ofpregnant women, 39.3% were primary school graduates. Pregnant women's meanduration of marriage is 6.5±4.9 years. Unintended pregnancy rate is 21.7%. The mean number ofpregnancies is 2.6±1.5. Pregnant women who give birth by caesarean section rateis 27%. Additionally, 15% of thepregnant have a chronic disease and 6.6 of them are smoker. According to SF-36quality of life form scales; there was a significant difference between thosewho are educated on primary education, those who have regular income, those whoare willingly pregnant in vitality, mental health, social functioning areas;spousal primary school education and the presence of social security in mentalhealth, vitality and pain scores. In addition, scores of physical function,physical and emotional role, mental health and social functioning weresignificantly lower in smokers.Conclusion: In our study it has been observedthat the level of education affects many measures of quality of life. Regularincome and social security have significantly affected the quality of life. Inaddition, a healthy pregnancy process is possible in women who have intendedpregnancy.